What prevents young adolescents from smoking?: self-reported motives of 12-15-year-old non-smokers - Schneider, Sven; Steins-Löber, Sabine; Janßen, Maria; Röhrig, Silke; Solle-Haertl, Denise (Health policy, 2010)
This study investigated the real motives of German non-smokers. In the German SToP (“Sources of Tobacco for Pupils”) Study 707 non-smoking pupils were asked to write down their motives for being non-smokers. A total of 1324 partially very elaborate free text statements (mean/range: 1.9/1-7 distinguishable motives) were evaluated in a qualitative content analysis.
Online veröffentlicht am 22. November 2009
Gesehen am 21.06.2023